Law-abiding versus criminal identity and self-efficacy: a quantitative approach to unravel psychological factors supporting desistance from crime - Oberlader, Verena A. (Psychology, crime & law, 2024)
Previous studies suggest that the process of becoming desistant from crime is accompanied by a shift from criminal to law-abiding identity and by the development of self-efficacy for law-abiding behavior. Utilizing self-report measures and an Implicit Association Test we predicted that a) a stronger law-abiding relative to criminal identity and a stronger/weaker self-efficacy for law-abiding/criminal behavior will correlate with lower actuarial recidivism risk at T1 and b) will explain variance in desistance two to three years later at T2. Results from a probation offender sample (N = 325) largely confirmed cross-sectional associations at T1. Univariately, self-reported and latency-based measured identity for law-abiding relative to criminal behavior explained variance in (survival time until) recidivism at T2 as opposed to self-efficacy for law-abiding or criminal behavior. Multivariately, self-reported law-abiding relative to criminal identity explained variance in survival time until recidivism beyond actuarial recidivism risk at T2. Further analyses showed that actuarial recidivism risk increasingly overestimated the risk to reoffend as the strength of law-abiding relative to criminal identity increased. The findings indicate that the strength of law-abiding relative to criminal identity plays a role in persisting in or desisting from criminal behavior. Yet, further research is necessary to identify the causal psychological mechanisms.